1984
DOI: 10.1152/ajprenal.1984.246.1.f12
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in glomerular function in rats developing spontaneous hypertension

Abstract: Clearance and micropuncture studies were conducted on 6-wk-old spontaneously hypertensive rats (SHR) of the Okamoto-Aoki strain and normotensive Wistar-Kyoto rats (WKY) under euvolemic conditions. Mean arterial pressure in SHR was elevated by 18 mmHg and their kidneys were vasoconstricted with reduced blood flow; resistances in preglomerular vessels and efferent arterioles were elevated 2.8 and 2 times, respectively, above WKY values. Whole kidney glomerular filtration rate (GFR) and single nephron glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
5
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 0 publications
9
71
5
1
Order By: Relevance
“…This finding differs from those of Dilley and colleagues 27 n and others, 29 who reported that GFR and RBF were markedly reduced in 6-to 9-week-old euvolemic SHR compared with WKY. They suggested that the renal vasoconstriction in the SHR was due to an enhanced tubuloglomerular feedback response.…”
contrasting
confidence: 98%
“…This finding differs from those of Dilley and colleagues 27 n and others, 29 who reported that GFR and RBF were markedly reduced in 6-to 9-week-old euvolemic SHR compared with WKY. They suggested that the renal vasoconstriction in the SHR was due to an enhanced tubuloglomerular feedback response.…”
contrasting
confidence: 98%
“…6 -7 ' 20 The results of the present study indicate that the intermediate ILA segment exhibits an augmented myogenic response that may also contribute to the increased preglomerular resistance, especially of superficial glomeruli. It is tempting to speculate that the enhanced vasoconstriction of the intermediate ILA acts in concert with afferent arteriolar vasoconstriction to prevent or attenuate elevated glomerular capillary pressure in superficial nephrons.…”
Section: Altered Pressure Response Of the Interiobular Artery In Sponmentioning
confidence: 61%
“…34 -36 A lower whole kidney glomerular filtration rate has also been reported in SHR during the a. development of hypertension. 37 All this accumulated evidence suggests that abnormalities in renal function may be involved in the pathogenesis of hypertension in SHR, more so when kidneys transplanted from SHR into Fl hybrids significantly raise blood pressure in the latter. 38 SHR are known to respond with exaggerated natriuresis when challenged with an acute sodium load 353940 ; however, this response is abolished when renal perfusion pressure is acutely reduced to normotensive levels, 40 -42 mainly through a decrease in the glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%